Accounting in 2036: A Learned Profession - Christensen, John (The Accounting Review, 2018)
ABSTRACT My assignment is to analyze the development of accounting thought and its position within the university. The focus is on the expected development in the next 20 years, despite the fact that that is an impossible task. I will ruthlessly extrapolate from my personal observations of the activities in the accounting community. In doing this, I will deal with accounting research, the relationship between research and teaching within the field of accounting, and the relation to other disciplines in the business school. This will be done in three steps. I will give a brief review of the recent history of accounting thoughts, then comment on current status of 2016, and, finally, give some perspectives. The road ahead is going to be bumpy as many institutional barriers are in the way. This has to change for the accounting academics to retake their space in the academic community.